Human Resource Competence and Internal Control Systems in Regional Government Financial Reporting: A Systematic Review - Sinosi, Sayidah Maryam; Prayitno, Andi; Nirwana, Nirwana; Darmawati, Darmawati (INVOICE : JURNAL ILMU AKUNTANSI, 2025)
This study aims to examine the influence of human resource (HR) competence and internal control systems on the quality of regional government financial reports, addressing the lack of integrated findings in recent literature. Using a Systematic Literature Review (SLR) approach, 25 peer-reviewed articles published between 2019 and 2024 were selected from academic databases based on relevance and methodological rigor. The review reveals that HR competence—particularly in financial knowledge, professional experience, and adherence to accounting standards—significantly improves reporting accuracy. Moreover, the presence of robust internal control systems plays a critical role in monitoring processes, ensuring regulatory compliance, and reducing the risk of fraud. The study highlights the importance of integrating qualified HR and strong internal controls to promote transparency and accountability in regional government financial management. These findings provide strategic insights for public sector policymakers and lay the groundwork for future research on financial governance.